2020
DOI: 10.1111/ced.14225
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast in benign chronic pemphigus (Hailey–Hailey disease)

Abstract: The current coronavirus disease (COVID-19) has forced the shutdown of many nonessential services in most high-risk countries. Most Dermatology consultations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…4,5 Few reports have been published on patients with refractory HHD who experienced marked improvement after treatment with apremilast, 2,3 however, it is not always successful. This lack of response has been noted in other series such as Riquelme-Mc Loughlin et al 6 and question the magnitude of the positive results seen to date (Table 1). Clinical response to apremilast may be limited to those locations where sweating is a well-known aggravating factor, hence the importance of complementing the treatment with other rescue therapies.…”
mentioning
confidence: 47%
“…4,5 Few reports have been published on patients with refractory HHD who experienced marked improvement after treatment with apremilast, 2,3 however, it is not always successful. This lack of response has been noted in other series such as Riquelme-Mc Loughlin et al 6 and question the magnitude of the positive results seen to date (Table 1). Clinical response to apremilast may be limited to those locations where sweating is a well-known aggravating factor, hence the importance of complementing the treatment with other rescue therapies.…”
mentioning
confidence: 47%
“…Furthermore, Yoto et al reported two cases of HHD treated with apremilast with no recurrence for up to 2 years (Yoto et al, 2021). On the other hand, Riquelme-Mc Loughlin et al (2020) used apremilast with five patients, but none of them showed any improvement. Apremilast was similarly ineffective in Case 2, even though it was less severe than Case 1.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been 13 reported cases of HHD treated with apremilast, including our own, as shown in Table 1. [3][4][5][6] None of the previous reports included information regarding any mutation in the ATP2C1 gene. According to the previous reports, the severity of the skin lesion was described in 11 of 13 cases; nine cases were classified as severe and two cases were classified as moderate.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recently, treatment with apremilast for a skin lesion of HHD has been reported. [3][4][5][6] We herein report two cases of HHD effectively treated with apremilast and review the previous literature.…”
mentioning
confidence: 99%